Strategi komunikasi dalam kalangan pelajar bahasa Arab di Jakarta / Ma'sum Mohammad - Mohammad, Ma'sum (2012)
This study focuses on the following: (a) levels of use of communication strategies among students at the Institute for Islamic and Arabic Sciences (LIPIA) in Jakarta, Indonesia (b) types of communication strategies used by students based on Tarone’s taxonomy (1977) (c) factors that encourage students to communicate in Arabic. The subjects consist of 30 students who follow the Arabic language preparation program (I'dad lughawi) at the Institute. This study is important because there are still many students in the LIPIA who are not able to speak Arabic well even though they have been studying it for a number of years. The study uses a both the mixed methods approaches in analyzing the data to answer the research question. The instrument used were (a) a set of interview questions for gathers quantitative data (b) a video recording of the oral activity for gathers quantitative data. The study found that the use of Arabic communication strategies of LIPIA students is high. Meanwhile students’ motivation and teachers’ encouragement given to student proved to be important factors that serve to encourage the students to communication in Arabic. The study also found that the oral activity used by the students namely B group (less proficient learners) consist of the avoidance strategies in Tarone Taxonomy. Whereas the A group (the more advanced learners) uses more of the paraphrase strategy in Tarone taxonomy. The most important findings of this study is the discovery of two communication strategies. They are (a) pauses and (b) repetition strategies. A model is thus proposed in this study, specifically the Arabic Model Communication Strategies, which may assist in the process of teaching and learning Arabic in Indonesia.